Stabilization of the front at frontal copolymerization of acrylamide with sodium acrylate in aqueous solutions - Salamevich, Alena A.; Hryniuk, Yauheni V.; Krul, Leonid P. (Journal of the Belarusian State University. Chemistry, 2020)
The objects of research were the process of frontal copolymerization of acrylamide with sodium acrylate in aqueous solutions, as well as the copolymers and hydrogels thus obtained. It has been shown that the frontal polymerization of acrylamide with sodium acrylate in an aqueous solution of high molecular weight polyacrylamide helps to reduce the initiator concentration necessary for the process and the formation of non-crosslinked copolymers. The effect of the addition of aerosil in the initial reaction mixture on the parameters of the copolymerization process and on the properties of the products formed is studied. The values of water absorption and gel fractions of the obtained hydrogels were determined.